2021
DOI: 10.1007/s11605-021-05036-8
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Evaluation of Short-Term Outcomes After Synchronous Colorectal Cancer Surgery: a Dutch Population-Based Study

Abstract: Background Synchronous colorectal cancer (CRC) has been associated with higher postoperative morbidity and mortality rates compared to solitary CRC. The influence of improved CRC care and introduction of screening on these outcomes remains unknown. This study aimed to evaluate time trends in incidence, population characteristics, and short-term outcomes of synchronous CRC patients at the population level over a 10-year time period. Methods Data of all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Studies have shown that some tumor morphology is more common in patients with synchronous tumors. 2 , 16 , 17 Index tumors of synchronous cases were more frequently moderately differentiated, mucinous adenocarcinoma, more deeply penetrated, and more often ulcerated, while concurrent lesions were less advanced. 18 Our results reproduced Oya et al’s 18 report.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies have shown that some tumor morphology is more common in patients with synchronous tumors. 2 , 16 , 17 Index tumors of synchronous cases were more frequently moderately differentiated, mucinous adenocarcinoma, more deeply penetrated, and more often ulcerated, while concurrent lesions were less advanced. 18 Our results reproduced Oya et al’s 18 report.…”
Section: Discussionmentioning
confidence: 95%
“…For SCRC that is distributed in multiple segments, the required extent of the procedure for tumors has remained controversial in the past decades. 17 , 19 Existing research demonstrated that there is no benefit in the survival of subtotal colectomy; therefore, segmental resection should be performed whenever possible. 20 In our study, most patients underwent multiple segment resection or extended resection, consistent with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SMPCC patients are more likely to suffer from postoperative complications and early death than SPCRC as they tend to require more extensive surgery. 9,17 Therefore there is a need to identify survival risk factors for SMPCC to optimize the treatment for these patients. To the best of our knowledge, this is the rst study to construct a prognostic prediction nomogram that could be used to predict all-cause and cancer-speci c early death in patients with resected SMPCC.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, patients with SMPCC tend to have a higher incidence of postoperative complications and mortality than those diagnosed with SPCRC. 9 However, although numerous studies have evaluated the long-term prognosis of SMPCC, relatively few studies have assessed the short-term outcome. [10][11][12] As a result, there is currently no effective tool that could be used to predict short-term mortality for SMPCC patients.…”
mentioning
confidence: 99%